Does Turbulence along the Coronal Current Sheet Drive Ion Cyclotron Waves? - Daniele Telloni; Gary P. Zank; Laxman Adhikari; Lingling Zhao; Roberto Susino; Ester Antonucci; Silvano Fineschi; Marco Stangalini; Catia Grimani; Luca Sorriso-Valvo; Daniel Verscharen; Raffaele Marino; et al. (The Astrophysical Journal, 2023)
Evidence for the presence of ion cyclotron waves (ICWs), driven by turbulence, at the boundaries of the current sheet is reported in this paper. By exploiting the full potential of the joint observations performed by Parker Solar Probe and the Metis coronagraph on board Solar Orbiter, local measurements of the solar wind can be linked with the large-scale structures of the solar corona. The results suggest that the dynamics of the current sheet layers generates turbulence, which in turn creates a sufficiently strong temperature anisotropy to make the solar-wind plasma unstable to anisotropy-driven instabilities such as the Alfvén ion cyclotron, mirror-mode, and firehose instabilities. The study of the polarization state of high-frequency magnetic fluctuations reveals that ICWs are indeed present along the current sheet, thus linking the magnetic topology of the remotely imaged coronal source regions with the wave bursts observed in situ. The present results may allow improvement of state-of-the-art models based on the ion cyclotron mechanism, providing new insights into the processes involved in coronal heating.